Perillaldehyde Controls Postharvest Black Rot Caused by Ceratocystis fimbriata in Sweet Potatoes - Zhang, Man; Liu, Man; Pan, Shenyuan; Pan, Chao; Li, Yongxin; Tian, Jun (Frontiers in Microbiology, 2018)
Black rot caused by Ceratocystis fimbriata is the most damaging postharvest disease among sweet potatoes. Black rot can be controlled by synthetic fungicides, but these synthetic fungicides also have several negative effects. Perillaldehyde (PAE), a major component of the herb perilla, is an effective and eco-friendly method of controlling this disease. The antifungal activity of PAE on the mycelial growth in C. fimbriata was evaluated in vitro. Sweet potatoes at the postharvest stage were surfaced-disinfected with 75% ethanol. Artificially created wounds were inoculated with a C. fimbriata cell suspension, and then, the PAE was spontaneously volatilized inside the residual airspace of the containers at 28◦C. Samples were collected at 0, 3, 6, 9, 12, 15, 18, and 21 days from each group, and the tissues around the wounds of the sweet potatoes were collected using a sterilized knife and then homogenized to determine their defense-related enzyme activity and quality parameters. In vitro assays showed that the mycelial growth of C. fimbriata was inhibited by PAE in a dose-dependent manner. An in vivo test demonstrated that 25 μl/l, 50 μl/l, and 100 μl/l PAE doses, when applied to sweet potatoes inoculated with C. fimbriata, could remarkable lower lesion diameter as compared to the control. Even though the storage time was prolonged, PAE vapor treatment still drastically inhibited sweet potato decay during storage at 28°C. These PAE vapor treatments also enhanced the activities of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), peroxidase (POD), polyphenol oxidase (PPO), and phenylalanine ammonia-lyase (PAL). These treatments remarkably decreased weight loss rates and had minor effects on other fruit quality parameters, such as anthocyanin content and vitamin C content. In our study, the results suggested that the effects of PAE on postharvest sweet potatoes may be attributed to the maintenance of enzymatic activity and fruit quality. In sum, PAE may be a promising approach to controlling C. fimbriata in sweet potatoes.